Image quality evaluation of chest for computed radiography - Velo, A. F. [UNESP]; Miranda, Diana Rodrigues de Pina [UNESP]; Duarte, S. B.; Alvarez, M. [UNESP]; Oliveira, M. [UNESP]; Ribeiro, Sergio Marrone [UNESP]; Miranda, J. R. [UNESP] (Springer Nature, 2013)
The daily-to-day of medical practice is marked by a constant search for an accurate diagnosis and therapeutic assessment. For this purpose the doctor serves up a wide variety of imaging techniques, however, the methods using ionizing radiation still the most widely used because it is considered cheaper and above all very efficient when used with control and quality. The optimization of the risk-benefit ratio is considered a major breakthrough in relation to conventional radiology, though this is not the reality of computing and digital radiology, where Brazil has not established standards and protocols for this purpose. This work aims to optimize computational chest radiographs (anterior-posterior projection-AP). To achieve this objective were used a homogeneous phantoms that simulate the characteristics of absorption and scattering of radiation close to the chest of a patient standard. Another factor studied was the subjective evaluation of image quality, carried out by visual grading assessment (VGA) by specialists in radiology, using an anthropomorphic phantom to identify the best image for a particular pathology (fracture or pneumonia). Quantifying the corresponding images indicated by the radiologist was performed from the quantification of physical parameters (Detective Quantum Efficiency - DQE, Modulation Transfer Function - MTF and Noise Power Spectrum - NPS) using the software MatLab®. © 2013 Springer-Verlag.
Keywords: Computed Radiography; Detective Quantum Efficiency; Modulation Transfer Function; Noise Power Spectrum; Visual Grading Assessments; Absorption and scatterings; Anthropomorphic phantoms; Computed radiography; Detective quantum efficiency; Image quality evaluation; Noise power spectrum; Subjective evaluations; Visual grading; Biomedical engineering; Image quality; Ionizing radiation; MATLAB; Modulation; Optical transfer function; Optimization; Physics; Power spectrum; Radiography; Radiology; Quality control